2020
DOI: 10.1021/acsmaterialslett.0c00209
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine-Induced Dual Defects in Cobalt Phosphide Nanosheets Enhance Hydrogen Evolution Reaction Activity

Abstract: Introduction of defects in a controllable way is important to modulate the electronic structure of catalysts towards enhancement of electrocatalytic activity. Herein, we report that fluorine incorporation into cobalt phosphide alloy has a unique effect -it creates both F-anion doping and P vacancy, which results in nearly 15-fold enhancement in catalytic activity for hydrogen evolution reaction (HER) in neutral solution. The existence of dual defects in CoP is confirmed by extended X-ray absorption fine struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(44 citation statements)
references
References 45 publications
0
41
0
Order By: Relevance
“…The rising absorption edge position of Co–P NBs is lower than that of Co(OH) 2 but higher than that of Co foil, suggesting that the average valence state of Co centers in Co–P NBs is slightly lower than +2. 12,23,59,66 To further explore the local electronic structure of the as-prepared catalysts, the XANES spectrum of Co–P NBs was calculated using ab initio finite difference methods using the model structure defined in the PDF card No. 29-0497 (S. G. Pnma ) as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The rising absorption edge position of Co–P NBs is lower than that of Co(OH) 2 but higher than that of Co foil, suggesting that the average valence state of Co centers in Co–P NBs is slightly lower than +2. 12,23,59,66 To further explore the local electronic structure of the as-prepared catalysts, the XANES spectrum of Co–P NBs was calculated using ab initio finite difference methods using the model structure defined in the PDF card No. 29-0497 (S. G. Pnma ) as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2a presents ex situ Co K-edge X-ray absorption near-edge structure (XANES) spectra of Co-P NBs, Co@CoFe-P NBs, Co@CoFe-O NBs, and the references Co foil, Co(OH) 2 , Co-FeOOH, Co 3 O 4 , and CoOOH. The rising absorption edge position of Co-PNBs is lower than that of Co(OH) 2 but higher than that of Co foil, suggesting that the average valence state of Co centers in Co-P NBs is slightly lower than +2 12,23,59,66. To further explore the local electronic structure of the as-prepared catalysts, the XANES spectrum of Co-P NBs was calculated using ab initio finite difference methods using the model structure defined in the PDF card No.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…This nanostructured material with dual effects of doping and creating P-vacancies exhibited the best catalytic performance with the requirement of a small overpotential 108 mV at 10 mA cm −2 . [118] Chen et al demonstrated the role of anion for enhancing the HER activity in NiP 1.92 Se 0.08 catalyst through Fourier-transformed-extended X-ray absorption fine structure (FT-EXAFS) studies. The catalyst exhibited HER overpotential of 81 mV to drive the current density of 10 mA cm −2 .…”
Section: Performance Of Nanostructured Mps For Hermentioning
confidence: 99%
“…117 As a result of their excellent chemical stability and electrical conductivity, transition metal phosphides (TMPs) have gained further consideration in HER research than transition metal oxides or suldes. [118][119][120] As a result, they are referred to as "quasi-platinum (Pt) catalysts". 121,122 Many methods have been used to make TMPs, including hydrothermal reactions, solvothermal reactions, electrodeposition methods, gamma-ray irradiation methods, and chemical vapor deposition (CVD).…”
Section: Nanosheets (Nss)mentioning
confidence: 99%